(untitled) (Research, Society and Development, 2020)
The present work aims to analyze the nullitatis dispute from its historical origin, from a brief analysis of the plans of existence, validity and effectiveness, of the correlation with the procedural assumptions and the respective hypotheses of fit. With the delimitation of the legal framework of the procedural institute and found that one of its characteristics leads to imprescriptibility, we investigate the (in) compatibility of the procedural institute with the constitutional values ​​and norms, notably with the postulate of legal security, considered one of the pillars of the Democratic State of Law, in view of the latent conflict that may arise from the possibility of eternal rediscussion of the cause. For this purpose, the deductive method is used, based on a general and principiological concept of legal certainty and its particular application in the specific case of the nullitatis dispute. The study will be based on bibliographic research and analysis of academic articles, legislation and jurisprudence, with an exploratory and propositional methodological objective.